Makna Lagu Ana al-‘Abdu Karya Mishary Rashid Alafasy (Studi Analisis Semiotik) - Aini, Qurrotul; Zaini, Hisyam (Universitas Muhammadiyah Gorontalo, 2023)
This study aims to analyze lyrics of Ana al-'Abdu, a song written by Mishary Rashid, using Charles Sanders Peirce's theory of Semiotics. The analysis will focus on Peirce's concept of trichotomy which includes icon, index, and symbol. The data were collected by copying lyric of the song from Arfan’s blogspot which mentions song’s lyric and its Indonesian translation. Secondary data were obtained from many sources such as; theses, articles, journals, books, and everything related to this research. As a qualitative writing, this article analyzes data by interpreting words and sentences of the song using Peirce’s theory descriptively. The analysis of the data is done through the description of meanings embodied in its words or sentences. As a result, this research finds that this song has a deep meaning of a sinful person who wants to repent, but his/her wishful thinking has protected him/her from doing so.